2018
DOI: 10.3390/ijms19103167
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Selenium with Chemotherapy and Radiation on Normal and Malignant Human Mononuclear Blood Cells

Abstract: Selenium, a trace element with anticancer properties, can reduce harmful toxicities of chemotherapy and radiotherapy without compromising efficacy. However, the dose-response relationship in normal versus malignant human cells is unclear. We evaluated how methylseleninic acid (MSA) modulates the toxicity and efficacy of chemotherapy and radiation on malignant and non-malignant human mononuclear blood cells in vitro. We specifically investigated its effects on endoplasmic reticulum stress induction, intracellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…However, higher doses of selenium may be toxic for both normal and malignant cells. 84 Similar results were observed for selenium nanocomposites. 85,86 A study showed that selenium has a synergic effect on the response of rat's glioma cells to ionizing radiation.…”
Section: Synergic Effects Of Selenium In Cancer Response To Radiationsupporting
confidence: 71%
See 1 more Smart Citation
“…However, higher doses of selenium may be toxic for both normal and malignant cells. 84 Similar results were observed for selenium nanocomposites. 85,86 A study showed that selenium has a synergic effect on the response of rat's glioma cells to ionizing radiation.…”
Section: Synergic Effects Of Selenium In Cancer Response To Radiationsupporting
confidence: 71%
“…It has been revealed that low doses of selenium protect normal mononuclear cells, while it has a toxic effect on malignant mononuclear cells. However, higher doses of selenium may be toxic for both normal and malignant cells . Similar results were observed for selenium nanocomposites .…”
Section: Synergic Effects Of Selenium In Cancer Response To Radiationsupporting
confidence: 67%
“…In a recent study, Methylseleninic acid has exhibited substantial cytotoxic effects toward monocytic leukemia cells (THP1) when likened with the healthy peripheral blood mononuclear (PBM) cells. In dose-dependent manner at various concentrations (2.5, 5, and 15 µM for 48 h), Methylseleninic acid showed improved anticancer activity against the malignant THP1 cells (Lobb et al 2018).…”
Section: Methylseleninic Acidmentioning
confidence: 99%
“…In vivo and in vitro studies have indicated that MSA is an excellent anticancer agent comparable to SeMet or selenite against a range of cancer models, including lung [102], breast [103,104], melanoma [105], and prostate cancer in particular [106,107,108]. In a recent study, MSA showed significant cytotoxic effects toward monocytic leukemia cells (THP1) compared with the healthy peripheral blood mononuclear (PBM) cells [109]. MSA also enhanced the anticancer activity of radiation and chemotherapeutic drugs (cytosine arabinoside and doxorubicin) in the malignant THP1 cells in a dose-dependent manner (2.5, 5, and 15 µM for 48 h) [109].…”
Section: Se-containing Compounds and Their Usage In Oncologymentioning
confidence: 99%